The Usage of Human IGHJ Genes Follows a Particular Non-random Selection: The Recombination Signal Sequence May Affect the Usage of Human IGHJ Genes - Shi, Bin; Dong, Xiaoheng; Ma, Qingqing; Sun, Suhong; Ma, Long; Yu, Jiang; Wang, Xiaomei; Pan, Juan; He, Xiaoyan; Su, Danhua; Yao, Xinsheng (Frontiers in Genetics, 2020)
The formation of the B cell receptor (BCR) heavy chain variable region is derived from the germline V(D)J gene rearrangement according to the “12/23” rule and the “beyond 12/23” rule. The usage frequency of each V(D)J gene in the peripheral BCR repertoires is related to the initial recombination, self-tolerance selection, and the clonal proliferative response. However, their specific differences and possible mechanisms are still unknown. We analyzed in-frame and out-of-frame BCR-H repertoires from human samples with normal physiological and various pathological conditions by high-throughput sequencing. Our results showed that IGHJ gene frequency follows a similar pattern which is previously known, where IGHJ4 is used at high frequency (>40%), IGHJ6/IGHJ3/IGHJ5 is used at medium frequencies (10∼20%), and IGH2/IGHJ1 is used at low frequency (<4%) under whether normal physiological or various pathological conditions. However, our analysis of the recombination signal sequences suggested that the conserved non-amer and heptamer and certain 23 bp spacer length may affect the initial IGHD-IGHJ recombination, which results in different frequencies of IGHJ genes among the initial BCR-H repertoire. Based on this “initial repertoire,” we recommend that re-evaluation and further investigation are needed when analyzing the significance and mechanism of IGHJ gene frequency in self-tolerance selection and the clonal proliferative response.